Przedstawienia rękawic płytowych na Poliptyku Grudziądzkim - Sokoliński, Adam (Acta Universitatis Lodziensis. Folia Archaeologica, 2012)
Hand defenses from the early 1420s consisted of plate gauntlets whose elements were riveted to the leather base. First mentions about gauntlets created from small metal plates appeared in the last decade of the 13th c. One of gives a description about gauntlets made by the armourers in Paris in 1296, which were made in the same manner as coat-of-plates. Metal plates were riveted to the textile or leather base or between layers of material. In form they were familiar to the pieces which can often be seen on illuminations or tombstones from first quarter of the 14th c. in Western Europe. They remained in common use until the third quarter of this century. Around the year 1350 demi-gauntlets similar in shape to hourglass appeared. They were usually created from one piece of metal. They protected the wrist and had usually anatomically formed metacarpus. Fingers were protected by small overlapping metal scales riveted to the leather stripes which were attached to the gauntlet’s metacarpus. After the year 1370, demi-gauntlets became the dominant form of hand protection.